Pengaruh Kepuasan Kerja dan Produktivitas terhadap Kinerja Kerja Secara Hybrid pada Bagian Keuangan di PT. Asuransi Jiwa Generali Indonesia - Mariana, Juwita; Purwatiningsih Purwatiningsih (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to analyze the influence of job satisfaction and productivity on hybrid work performance at PT Asuransi Jiwa Generali Indonesia, especially in the Finance department. The method used is descriptive quantitative with data collection techniques through questionnaires and documentation. The research sample amounted to 66 respondents. There are three main variables: X1 (Job Satisfaction), X2 (Productivity), and Y (Work Performance). The results of the analysis showed that partially, job satisfaction had a significant effect on work performance, as evidenced by a probability value of 0.000 < 0.05 and a Thcal value of 5.437 > Ttable 1.99834. Productivity also showed a partially significant influence on work performance, with a probability value of 0.000 < 0.05 and a Thcount of 4.213 > Ttable 1.99834. Simultaneously, job satisfaction and productivity have a significant effect on work performance, as shown by the results of the F test with a probability value of 0.000 < 0.05 and Fcal 998.377 > Ftable 3.14. These findings confirm that increasing job satisfaction and productivity simultaneously can drive more optimal work performance in a hybrid work system. The practical implication of this research is the need for a managerial strategy that focuses on improving employee well-being and work efficiency to support organizational performance on a sustainable basis.